Analisis Minat Beli Ulang pada Sektor Usaha Kuliner - Pebriana, I Kadek Dwi Putra; Oktarini, Luh Nik (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This study aims to determine the effect of product quality and service quality on customer satisfaction and repurchase interest. This research was conducted at the Sentana Jahen Restaurant located in Penatih Village, East Denpasar District, Denpasar. The population in this study was 13,446 customers and by using the Slovin formula, the sample size was determined to be 99 people using the accidental sampling technique. Data was collected by interview and questionnaire method using a five-choice Likert Scale. After testing the instrument, it is continued with partial hypothesis testing using path analysis and Sobel test to test the role of customer satisfaction as a mediating variable. The results of the analysis prove that all the hypotheses proposed are acceptable and customer satisfaction can increase the influence of product quality and service quality on repurchase interest.